Colangiopancreatografia retrógrada endoscópica por coledocolitíase no Hospital Universitário Walter Cantídio-UFC : avaliação de 56 casos - Matos, Diego da Costa (2020)
Choledocholithiasis is the most frequent cause of biliary obstruction commonly seen in gastroenterological practice. Objective: evaluate the rate and factors related to success and complications in patients with choledocholithiasis, referred or ERCP in HUWC- UFC. Methodology: Retrospective study of 56 patients submitted to 67 examinations for choledocholithiasis from 01/2017 to 04/2018. The information was taken from the Endoscopy unit medical records database. Success rates (complete withdrawal of calculus), complications (pancreatitis, hemorrhage and perforation), and factors related to these outcomes were analyzed. CEP: 43321014.6.0000.5045. Results: There was a predominance of women (80%), in their early 50 years old. The success rate was 89%. With surgical therapeutic complementation in 9%. 2% of the cases are still under follow-up. The most frequent complication was pancreatitis (7%), being (1) patient with evolution to death (1.8%) without perforations or bleeding. There was an association between the presence of large stones (p = 0.05) and bile duct disproportion (p = 0.01) with ERCP failure. There was no association of the factors evaluated, with the presence of complications. Conclusion: The study shows that there was a high success rate, as described in the literature. The presence of large stones and disproportion, factors related to ERCP failure.